Offender profile - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Profiling is making inferences about the possible characteristics of an offender from the available data. Despite its popularity among the public and use by law enforcement in investigations, the legal definition of profiler, the skills a profiler should have, and the scientific validity of profiling methods are still debated. The lack of legal definitions can be related to the inability to follow practices to a certain standard and the continuing uncertainty regarding the ethical responsibilities. The fact that the profiling process includes uncertainties due to its nature can make the process vulnerable to errors that may cost individuals their rights and freedoms. A profiler should be under an obligation to be aware of the scientific bases he uses, be able to reflect on the cognitive biases, be aware of the weaknesses of the data and methods he uses, and bear a professional and ethical responsibility. The generalizability of the research results can be strenthened by adding more profilers to the studies investigating the effectiveness of profiling. It is essential to create a scientific description of the competencies that a profiler should have and directly measure these competencies in research. Institutions that use profiling can prevent rights violations if they establish their ethical guidelines and ensure that they are followed. In this paper, the problems faced by profilers who reason and make decisions to evaluate complex criminal behavior are described in the context of psychological biases and ethical principles. © 2021 Nova Science Publishers, Inc.